0547 RLS Patient Odyssey Survey II. (25th May 2022) - Cinatl, Christopher; Ondo, William; Koo, Brian; Dzienkowski, Karla; Durmer, Jeffrey; Phelps, Charles; Winkelman, John
Abstract: Introduction: RLS affects 5%-10% of European and North American adults, with 2%-3% experiencing moderate to severe symptoms. RLS patients, often undiagnosed or improperly treated, experience significant depression in addition to loss of sleep. Methods: ODYSSEY II, an online and in-print self-administered questionnaire (respondents primarily from the United States) included validated questions on RLS diagnosis and severity, associated medical conditions, RLS treatment responses, access to RLS care, and standardized PHQ-9 depression measures. RLS status was confirmed using the Cambridge-Hopkins Questionnaire. Analysis included linkage of PHQ-9 depression scores to EQ-5D Health-Related Quality-of-Life (HRQoL) scores using externally validated methods. Results: Of 3, 003 online or mail-in participants, 2, 745 were RLS confirmed, 55% having severe symptoms (IRLS ≥ 21), 86% using medications and 73% reporting histories of dopaminergic augmentation (medication related worsening of symptoms).Of RLS-confirmed respondents, average PHQ-9 depression scores were 8.98 for women (US average 3.72) and 7.22 for men (US average 2.67). Among RLS patients, 29% of males and 40% of females (comparable US averages 11% and 6.5%) had PHQ-9 depression scores ≥ 10 (moderate, moderately severe or severe) a fourfold risk of important (≥ 10 score) depression. Suicidal ideation was reported by 15% of respondents (US average 4.0%). Associated EQ-5D scores show that 37% of all respondents had HRQoL scores below 50% of "full health."Of six drug classes used to treat RLS, three drug classes had patient-reported efficacy above 60%, but all had patient-reported drawbacks, ranging from weaker efficacy for some patients (alpha-2-delta ligands) to augmentation (dopaminergics, almost three-quarters of patients) and difficulties in obtaining prescriptions (opioids) for others.Respondents reported decade-plus delays from time of symptom onset to diagnosis, and still may remain improperly diagnosed or inadequately treated. Respondents managed by RLSF certified providers reported better outcomes. Conclusion: ODYSSEY II documents that depression, suicidal thinking and HRQoL losses are very significant among many RLS patients. Respondents report troubling delays from symptom onset to correct diagnosis. Survey results demonstrate that RLS related symptoms are best improved when patients use RLSF certified providers. Improved education to both primary care providers and patients may also lead to better patient outcomes. Support (If Any): Arbor Pharmaceuticals